Peran Pariwisata Desa Pandean terhadap Kesejahteraan Masyarakat Lokal - M. Zuhriyan Chilmi; Hendra Paratama (STIKes Ibnu Sina Ajibarang, 2024)
The aim of this research is to find out the role of the Pandean Tourism Village towards welfare of local communities. This research uses a qualitative and descriptive approach data, both primary data and secondary data. The first is observation and interview. Secondary data is BPS Trenggalek, Disbudpar, Dongko District and BPS East Java. The research results show that the presence of the Pandean Tourism Village provides impacts and benefits for local communities who are directly involved in activities such as tourism can provide and increase the income of local communities, provide business opportunities for local residents, providing employment, improving quality human resources and also provides benefits in introducing regional culture. Besides that, Pandean Tourism Village also creates prosperity for people who are directly involved in tourism activity. This was proven when researchers calculated people's income and its size the surrounding community has achieved prosperity or income is above the poverty line. When a small portion of the local community who are directly involved are still not involved prosperous because of the small number of visitors and so on, so their income is not there optimal or still below the poverty line. Meanwhile, the surrounding community does not those directly involved in tourism activities still do not feel the great benefits of tourism.